Practical plant failure analysis : a guide to understanding machinery deterioration and improving equipment reliability - Sachs, Neville W. (CRC Press/Taylor & Francis Group, 2019)
"This book is designed for engineering, and skilled trades personnel involved in improving machinery maintenance and reliability. It explains the four major failure mechanisms, wear, corrosion, overload, and fatigue, and how to identify them. Knowing the physical failure mechanics involved, the reader can then solve the physical and human causes. This new edition provides more detail and will include data on individual component failures. All chapters will be revised, all diagrams will be redrawn, new examples will be added to each of the diagnostic chapters, and the Fasteners and Bolted Joints chapter will be expanded to include other coupling designs"--